Strategy to Strengthen Internal Control System for State-Owned Property Administration (Case Study: Ministry of Energy and Mineral Resources) - Endito, Astria; Daryanto, Wiwiek M. (The Indonesian Journal of Business Administration, 2018)
Abstract - Establishing a transparent and accountable financial report and report on State-Owned Property, which referred to Bahasa Indonesia as Barang Milik Negara (BMN), or known as Good Governance, it is not easy. For that in need a good system of internal control of administration. Based on the above problems, this study aims to: 1) Knowing the causes of negative findings on the internal control system of the administration of BMN assets. 2) Knowing the quality of the implementation of the Internal Control System in the BMN Administration in the MEMR. 3) Propose a strategy of strengthen the Internal Control System in the BMN Administration in the MEMR. The method used in this research consists of three stages, first using descriptive method, the second using qualitative method using NVIVO and third using SWOT and QSPM method. The results of the analysis show: 1) Based on the report of BPK-RI audit result in the know that the administration of fixed assets in ESDM ministry has not been adequate, 2) Implementation of SPI administration in the Ministry of ESDM is still running less good than the five elements only information and communication that get good criteria 3) Strategy that must be implemented related to internal control system is to strengthen the internal control system by improving the quality of BMN report through updating of information technology and application of BMN management.Keywords: administration of state property, internal control system, SWOT analysis and QSPM analysis